PENGARUH LATIHAN MEGGUNAKAN RESISTANCE BAND TERHADAP KEMAMPUAN SHOOTING DALAM PERMAINAN FUTSAL SISWA SMA NEGERI 1 MALILI - Alla', Yusuf; Riswanto, Heri; Ulpi, Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The ability to shooting is an essential skill in futsal that determines the success of scoring goals. Improving this ability requires appropriate physical training to optimize muscle strength, coordination, and kicking accuracy. This study aims to determine the effect of resistance band training on shooting ability in futsal among students of SMA Negeri 1 Malili. The research employed a quantitative experimental method with a one group pretest-posttest design, in which initial measurements (pretest) were taken before the treatment and final measurements (posttest) after the treatment. The population consisted of all futsal extracurricular students at SMA Negeri 1 Malili (35 students), while the sample comprised 15 students selected through random sampling. The resistance band training program was conducted for six weeks with a frequency of three sessions per week, totaling 18 training sessions. Shooting ability was measured through a kicking test from a distance of 6 meters toward a futsal goal with predetermined target areas. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores, with an average increase of 7.40 points and a significance value of p = 0.000 (p < 0.05). The percentage increase in shooting ability was 46.25%, categorized as very good. It can be concluded that resistance band training is effective in improving leg muscle strength, coordination, and body stability, which directly contribute to enhancing shooting ability in futsal among SMA Negeri 1 Malili students.